Analisis Manajemen Risiko Pada UMKM Pertanian Menggunakan Pendekatan ISO31000 dan Matriks Risiko: Studi Kasus “Berkah Tani” - Anisa Roshy Rosdian; Aghnia Yasyfa; Hesti Hisani Latifah Hamdah; Sarah Mutia Azahra; Alfiana Alfiana (Indo Publishing, 2026)
The agricultural sector faces various risks that can threaten business continuity and sustainability. This study aims to analyze risk management in agricultural MSMEs